New Advanced Analytical Methodologies Developed for Quality Control of Herbal Extracts of Cuscuta Reflexa Roxb Formulation - Mohammed Minhajuddin (International Journal of Allied Medical Sciences and Clinical Research, 2023)
The quality control of plant products is a general requirement to be fulfilled. Good quality assurance is necessary when dealing with the plant products, intended to be released in market as drug constituents or as test substances in basic pharmacological experiments. objective of study: Quality control is crucial to ensure the safety and correct handling of herbal medicines. .The pharmaceutical approach of analyzing a single ingredient cannot be applied to discern the quality of herbal preparation. Thus, quality control methods which reflect the holistic approach of complementary medicine have to be developed in order to determine the chemical basis of herbal medicines. Plan of work: it includes, Selection of formulations, Physico-chemical evaluation of formulations, Description, Loss on drying, Moisture content determination by Karl-Fischer method, Total ash, Acid insoluble ash, Water soluble ash, pH of 1% solution, pH of 10% solution. Research methodology Selection of formulations Unani formulations to be included in Unani Pharmacopeia/Formulary. Results and discussion: Physico-chemical evaluations like organoleptic characteristics, loss on drying, ash content, extractive values etc. were carried. The HPTLC fingerprint analysis of methanol, chloroform and petroleum ether extracts of Itrifal-e-Aftimoon was carried out. Heavy metal analysis of arsenic, lead, mercury and cadmium was performed for all the test samples by using the atomic absorption spectrophometer. Calibration curve for each heavy metals were set to ensure the accuracy of the Atomic absorption spectrophotometer. Quantification of Aflatoxins in Itrifal-e-Aftimoon by HPLC-PDA By using the developed and validated extraction and HPLC-PDA methods of three different batches of Itrifal-e-Aftimoon were investigated. All the samples were successfully analyzed for the content of aflatoxins and found that the samples were free from aflatoxins and safe for the use. The mobile phase was selected using different compositions of methanol–water and acetonitrile– water; it was found that the all four aflatoxin are successfully separated by using a mixture of acetonitrile and water in 1:1, v/v composition. A simple rapid and economic simultaneous HPLC method was developed and validated for the quantification of gallic acid, ellagic acid and ascorbic acid.